Pengaruh Strategi Pembelajaran Terhadap Kecerdasan Emosional Dan Hasil Belajar Seni Musik Pada Siswa Kelas V SD Bali Public School Denpasar - ., DEWA GEDE SUJANA; ., PROF. DR. NYOMAN DANTES; ., DR. NI KETUT WIDIARTINI, S.Pd.,M.Pd (Jurnal Penelitian dan Evaluasi pendidikan, 2015)
Tujuan penelitian ini adalah untuk mengetahui perbedaan kecerdasan emosional dan hasil belajar seni musik antara siswa yang mengikuti pembelajaran dengan strategi pembelajaran akselerasi dan strategi pembelajaran ekspositori. Sebanyak 82 siswa kelas V SD Bali Public School Denpasar dipilih sebagai sampel. Penelitian ini menggunakan desain eksperimen The Posttest-Only Control Group Design. Data kecerdasan emosional dikumpulkan dengan menggunakan kuesioner dan data hasil belajar seni musik dikumpulkan dengan tes. Uji konsistensi internal butir kuesioner dan tes dianalisis dengan menggunakan Product Moment dan Point Biserial. Uji reliabilitas kuesioner dan tes dilakukan dengan menggunakan Alpha Cronbach dan KR-20. Uji hipotesis menggunakan MANOVA. Hasil penelitian menunjukkan bahwa: pertama, terdapat perbedaan kecerdasan emosional antara siswa yang mengikuti strategi pembelajaran akselerasi dan siswa yang mengikuti strategi pembelajaran ekspositori. kedua, terdapat perbedaan hasil belajar seni musik antara siswa dengan strategi pembelajaran akselerasi dan siswa dengan strategi pembelajaran ekspositori); ketiga, secara simultan terdapat perbedaan kecerdasan emosional dan hasil belajar seni musik antara siswa yang mengikuti strategi akselerasi dan siswa dengan strategi pembelajaran ekspositori. Kata Kunci : Strategi pembelajaran akselerasi, Strategi pembelajaran ekspositori, kecerdasan emosional, hasil belajar seni musik This research aims to investigate: First, the difference of emotional intelligence between students who learned using acceleration learning strategy and students who learned using expository learning strategy. Second, the difference of music learning achievement between students who learned using acceleration learning strategy and students who learned using expository learning strategy. Third, the difference of emotional intelligence and music learning achievement between students who learned using acceleration learning strategy and students who learned using expository learning strategy. This is an experimental research using Posttest-Only Control Group design. Population in this research was the entire fifth grade students SD Bali Public School Denpasar academic year 2014/2015 which consisted of experimental group (acceleration class) and control group (expository class). Sample was selected using random sampling technique with lottery method. Data were collected using test and analyzed using analysis of variance and Multivariate Analysis of Variance (MANOVA) with F-test. The results show that: First, there is a difference in emotional intelligence between students who learned using acceleration learning strategy and students who learned using expository learning strategy of fifth grade students SD Bali Public School Denpasar. Second, there is a difference in music learning achievement between students who learned using acceleration learning strategy and students who learned using expository learning strategy of fifth grade students SD Bali Public School Denpasar. Third, there is a difference in emotional intelligence and music learning achievement between students who learned using acceleration learning strategy and students who learned using expository learning strategy of fifth grade students SD Bali Public School Denpasar. keyword : acceleration learning strategy, expository learning strategy, emotional intelligence, and music learning achievement